The cultural mission of classical university - O. Y. Pavlova, (Ukrainian Cultural Studies, 2018)
The article is devoted to the analysis of historical dynamics of university and its classification of cultural types. The main part of attention is concerned over the classical model of university and its transformations. The university carries out a social institution. It has absence of its own an autonomous field of culture, which is a form of spiritual rather than social production. Education is a set of social institutions that produce the social structure directly, that is, social technology with the purpose of human and social production of the new model. The society of the late Modern becomes a collection of social institutions (not only educational, but also legal, political, economical, and even in a certain sense cultural) and industries (specialized fields of material production). Education in this sense is a form of human production in general, while economics, politics and law are generally aimed at the indirect production of people through the logic of much complicated institutes movement: economics, politics, law (goods, power structures and laws). Depending on the national model of education, universities determine the priority of certain educational strategies. The university as a social technology, based on the new sample of the anthropological model, forms disciplinary practices that function for production of habitus and cultural capital, and also provides identification "under the auspices of the concept of culture" (B. Readings) in the Modern era. This cultural-historical period is characterized by the fact that social control is carried out not with the help of personal coercion, but of the passage through institutions. A higher educational institution in the era of Modernity is the most consistent embodiment of the idea of a social institution as an intermediary between spiritual and material production. Culture in this context acts as a form of "high culture," that is, as a way of human existence just like this, with value orientations on the foundations of universal cult of reason. The "Cultural Mission" of the University is a mediation between the regulatory ideas of the Modern and a certain type of state that is, to be a social technology of nation-building. The technology of cultivating reason is provided by studying at the Philosophy Faculty and is an obligatory philosophical component for other faculties in the German model, created by V. Humboldt. The formation of the cult of universal reason and self-sufficient subject is the basic task of the classical university and its leading sociocultural function and cultural mission.
Keywords: university, classical model of university, cultural mission, social institute, cultural field, social technology